Channel characterization and modeling for GEO satellite-to-land terminals at ku-band with tropical weather awareness - Al-Saegh, Ali Mohammed Ali (2015)
Severe tropical weather dynamic impairments on the earth-sky signal quality at Ku-band compared to temperate weather have increased the demand for channel characterization and modeling for satellite-to-land terminals in tropical regions. Consequently, this will achieve improvement in identifying the type and the performance of the Fade Mitigation Technique (FMT), managing the available communication resources, and enhancing the reliability and efficiency of the communication link. The variation in weather dynamics decreases the accuracy of the existing Land Mobile Satellite (LMS) channel models when applied in tropical regions which may negatively impact the performance of the satellite networks in the tropical regions. This may also attributed to the lack of reliable investigations and studies on channel performance characterization, experiments, and analysis of the LMS channel in tropical regions under atmospheric impairments. Moreover, the existing LMS channel models do not consider several other essential issues in channel modeling. Therefore, it is necessary to design a comprehensive, reliable, and more accurate LMS channel model that considers these issues. To overcome such drawbacks: Firstly, we developed a signal attenuation prediction method for extracting the atmospheric impairments out of other impairments affecting signal quality for multi-regions in tropics, update the world’s database with the first measured data of some regions in the tropics, design and validate a new satellite-to-land mobile channel model at Ku-band with features that enhance accuracy, comprehensiveness, and reliability. Finally, the study proposed a tropical weather-aware LMS channel model that can be applied under different atmospheric (rain, clouds, and tropospheric scintillation) and mobility impairments. Furthermore, the resultant signal quality was evaluated for different modulation and coding schemes using an improved Quality Indicator Module (QIM) that is included in the proposed channel model. The results obtained show that the proposed method provides reliable multiregion channel performance analysis in the tropical regions. The method enables the system designer to accurately predict the atmospheric impairments on satellite link and signal quality performance with error rates during dynamic weather conditions in various tropical regions. Moreover, the proposed extended LMS channel (ELMSC) model during non-rainy and -cloudy environments, and the comprehensive satellite to tropical LMS channel (STROC) model that incorporates atmospheric dynamics, were proven to have lower Root Mean Square Error (RMSE), and higher reliability than the conventional models. The measured data were provided, and a significant agreement was observed between the proposed model and the measured data. The comparison of the performances of the proposed model with the measured channel performances confirms the reliability and the accuracy of the proposed ELMSC model with lower RMSE (reaches 0.0543 dB) than the conventional model (0.187 dB). Moreover, the proposed STROC model is shown to have lower RMSE (reaches 0.0072 dB) than the existing model with 0.0297 dB RMSE. The proposed channel models are suitable for analytical and numerical performance prediction and evaluation of various realistic atmospheric conditions and channel states, for narrow- and wide-band LMS systems, at various modulation and uncoded/coded schemes, and different satellite terminal speeds. The model and its associated modules can be used to study the signal performance, availability, and error rates of different services, including communications, broadcast, and navigation, as well as to develop a FMT for channel-aware strategies.